Endothelial repair capacity and apoptosis are inversely related in obstructive sleep apnea - Jelic, Sanja (Dove Medical Press, 2009)
PURPOSE: To investigate the impact of obstructive sleep apnea (OSA) on endothelial repair capacity and apoptosis in the absence of potentially confounding factors including obesity. PATIENTS AND METHODS: Sixteen patients with a body mass index <30 and newly diagnosed OSA and 16 controls were studied. Circulating levels of endothelial progenitor cells, a marker of endothelial repair capacity, and endothelial microparticles, a marker of endothelial apoptosis, were quantified before and after four-week therapy with continuous positive airway pressure (CPAP). Endothelial cell apoptotic rate was also quantified in freshly harvested venous endothelial cells. Vascular reactivity was measured by flow-mediated dilation. RESULTS: Before treatment, endothelial microparticle levels were greater and endothelial progenitor cell levels were lower in patients with OSA than in controls (P < 0.001 for both). Levels of endothelial microparticles and progenitors cells were inversely related (r = −0.67, P < 0.001). Endothelial progenitor cell levels increased after effective treatment (P = 0.036). CONCLUSIONS: In the absence of any co-morbid conditions including obesity, OSA alone impairs endothelial repair capacity and promotes endothelial apoptosis. These early endothelial alterations may underlie accelerated atherosclerosis and increased cardiovascular risk in OSA.